2019
DOI: 10.31219/osf.io/wb7sx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ferroelectret materials and devices for energy harvesting applications

Abstract: This paper provides an overview of ferroelectret materials for energy harvesting applications. These materials take the form of a cellular compliant polymer with polarised pores that provide a piezoelectric response to generate electrical energy as a result of an applied strain or surrounding vibration. The manufacturing processes used to create ferroelectret polymer structures for energy harvesting are discussed, along with the range of microstructural features and pore sizes that are formed. Their important … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 80 publications
(158 reference statements)
0
12
0
Order By: Relevance
“…Eight organic acids were chosen for study (Figure ) based on commercial market relevance: benzoic acid (BA), lactic acid (LA), levulinic acid (LVA), succinic acid (SA), salicylic acid (SLA), tartaric acid (TA), malic acid (MA), and citric acid (CA). Of these, benzoic acid and lactic acid are the most commonly used in commercial products at present. ,, The unadjusted pH values for all e-liquid formulations in this study are shown in Table . For studies on radical formation from nicotine salts with different types of organic acid conjugates, e-liquids were formulated at equimolar ratios (1:1) of nicotine to acid and adjusted to neutral pH using sodium hydroxide (NaOH) when required.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight organic acids were chosen for study (Figure ) based on commercial market relevance: benzoic acid (BA), lactic acid (LA), levulinic acid (LVA), succinic acid (SA), salicylic acid (SLA), tartaric acid (TA), malic acid (MA), and citric acid (CA). Of these, benzoic acid and lactic acid are the most commonly used in commercial products at present. ,, The unadjusted pH values for all e-liquid formulations in this study are shown in Table . For studies on radical formation from nicotine salts with different types of organic acid conjugates, e-liquids were formulated at equimolar ratios (1:1) of nicotine to acid and adjusted to neutral pH using sodium hydroxide (NaOH) when required.…”
Section: Methodsmentioning
confidence: 99%
“…E-liquid solutions containing nicotine salts are now considered the most popular e-liquids to vape with pods and disposable e-cigarette devices. Unlike e-liquids using freebase nicotine, nicotine salt solutions contain the addition of an organic acid or a mixture of organic acids to form an ionic pair, or a salt, with nicotine. Nicotine salt e-liquid solutions are often available with high concentrations of nicotine (up to 5% or 50 mg/mL) in a mixture of propylene glycol (PG) and vegetable glycerin (VG) . PG and VG are hygroscopic, and thus, water is also one of the most abundant components of e-liquids, present at up to 18 wt % in previously studied vape products. The pH of commercial nicotine salt e-liquids has been measured to be as low as 3.6, depending on the exact formulation of nicotine salt and ratio of the organic acid to nicotine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-liquid formulations with freebase (FB) nicotine, used for the metal coil material study, were prepared with 6 mg/mL nicotine (0.6% FB) in 30% propylene glycol (99%, from Sigma-Aldrich) and 70% vegetable glycerin (≥99.5% from Sigma-Aldrich) by volume (i.e., 30:70 PG/VG), with relevance to commercially available e-liquids. , Solutions were stored at 2–8 °C prior to use. E-liquid formulations with nicotine salts were prepared at 2% (w/w) or 20 mg/mL, with relevance to commercially available e-liquids (20–50 mg/mL concentration range). Benzoic acid (≥99.5%, from Sigma-Aldrich), was chosen as the acid for the nicotine salt (1:1 molar ratio with nicotine) , due to its popularity in commercial formulations. ,,− …”
Section: Methodsmentioning
confidence: 99%
“…4th gen pods or pod-mods, which have been recently introduced to the market and are popular among nicotine users, are designed to vape nicotine salts. 4th gen devices are also designed for more efficient nicotine delivery and can be purchased as refillable pods or prefilled pods in a range of formulations containing various organic acid additives and nicotine concentrations. …”
Section: Introductionmentioning
confidence: 99%